(untitled) (International Journal of Nursing Education, 2025)
Background: Nurses are considered a vulnerable group to experience stress and anxiety during the COVID-19 pandemic because of feelings of inadequate protection and high risks of infection. Being isolated from family, and dealing with the challenges including stigma and discrimination at the workplace and surroundings also increase the risk for such problems. Hence, this study aimed to find out nurses’ perceived stress and their social support for the personal and professional quality of life.Methods: A descriptive cross-sectional study was conducted among 224 nurses directly involved with caring of COVID-19 patients in university hospitals. A simple random sampling technique was applied to select the eligible participants and a self-administered structured questionnaire was used to collect data.Descriptive statistics (Percentage, mean, median, standard deviation) and inferential statistics were calculated by using IBM SPSS software version 21.Results: Out of 224 participants, 75.3% and 16.2% of the nurses perceived moderate and high levels of stress, respectively. Similarly, 65.6% perceived moderated and 31.3% had a high level of social support during the period of COVID-19 pandemic.Conclusions: Almost all nurses, who are providing direct patient care during the COVID-19 pandemic, had experienced moderate to high levels of stress, and all of them perceived a moderated to high level of social support during the pandemic